Analysis of the yeast nucleoporin Nup188 reveals a conserved S-like structure with similarity to karyopherins - Flemming, Dirk; Schwarz, Johannes; Amlacher, Stefan; Hurt, Ed (Journal of structural biology, 2012)
Nuclear pore complexes (NPCs) embedded in the double nuclear membrane mediate the entire nucleocytoplasmic transport between the nucleus and cytoplasm. Each NPC is composed of about 30 different proteins (nucleoporins or Nups), which exist in multiple (8, 16 or 32) copies within the NPC scaffold. Recently, we have identified and characterized the large structural Nups, Nup188 and Nup192, from the thermophilic eukaryote Chaetomium thermophilum, which exhibited superior properties for biochemical and structural studies, when compared to their mesophilic orthologs. Here, we study the large structural Nups from the model organism yeast Saccharomyces cerevisiae. Our data show that yeast Nup188 like its thermophilic orthologue ctNup188 exhibits a twisted S-like structure, which flexibly binds the linker nucleoporin Nic96 via a short conserved α-helix motif. Using bioinformatic methods, we have generated a pseudo-atomic structural model of Nup188 and its related Nup192, which further strengthens the view that the large α-solenoid structural Nups are related to karyopherins.
Available online 22 November 2011
Gesehen am 04.04.2018